If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(1x + 6) = 28 Reorder the terms: 7(6 + 1x) = 28 (6 * 7 + 1x * 7) = 28 (42 + 7x) = 28 Solving 42 + 7x = 28 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-42' to each side of the equation. 42 + -42 + 7x = 28 + -42 Combine like terms: 42 + -42 = 0 0 + 7x = 28 + -42 7x = 28 + -42 Combine like terms: 28 + -42 = -14 7x = -14 Divide each side by '7'. x = -2 Simplifying x = -2
| 4*(n*-3)=n-27 | | 3(-r)+5= | | c^8-15625c^2=0 | | 12.0x+10=34+9.9x | | a^6+32a=0 | | c+c*c=0.24 | | 3x^6-x^3-24=0 | | 3x^2+3=x | | 59-4x=14x+19 | | 3w+(3w+36)=84 | | 9x^2y^2+9xy+2= | | 5x-10=98+6x | | x^2y^2-3xy+2=0 | | 93=11x+5 | | 8+5x-11=3x-22+9x | | 3z^2-8z-16=0 | | 32m^2+14n^2-8-12m^2+5n-3= | | 5x=230 | | 2x+10=-110-10 | | 14a^2b^2+51ab+40= | | 90=37.54+0.50x | | 7x^2=46x-24 | | 3x+17-7x-36+6x=7 | | 6(x-11)=5 | | 15x^2+29xy-14y^2= | | 6-14x=-18 | | -25*25= | | 30x^2+19xy-28y^2= | | 5x+13=-7-7x | | x+5=10x+9 | | x=(4-(3-5(7-4)+3))+3 | | 75=300-3P |